Smart Drug Delivery Systems Based on Cyclodextrins and Chitosan for Cancer Therapy - Larisa Păduraru; Alina-Diana Panainte; Cătălina-Anișoara Peptu; Mihai Apostu; Mădălina Vieriu; Tudor Bibire; Alexandru Sava; Nela Bibire (Pharmaceuticals)
Despite improvements in therapeutic approaches like immunotherapy and gene therapy, cancer still remains a serious threat to world health due to its high incidence and mortality rates. Limitations of conventional therapy include suboptimal targeting, multidrug resistance, and systemic toxicity. A major challenge in current oncology therapies is the development of new delivery methods for antineoplastic drugs that act directly on target. One approach involves the complexation of antitumor drugs with cyclodextrins (CDs) and chitosan (CS) as an attempt to counteract their primary limitations: low water solubility and bioavailability, diminished in vitro and in vivo stability, and high dose-dependent toxicity. All those drawbacks may potentially exclude some therapeutic candidates from clinical trials, thus their integration into smart delivery systems or drug-targeting technologies must be implemented. We intended to overview new drug delivery systems based on chitosan or cyclodextrins with regard to the current diagnosis and cancer management. This narrative review encompasses full-length articles published in English between 2019 and 2025 (including online ahead of print versions) in PubMed-indexed journals, focusing on recent research on the encapsulation of diverse antitumor drugs within those nanosystems that exhibit responsiveness to various stimuli such as pH, redox potential, and folate receptor levels, thereby enhancing the release of bioactive compounds at tumor sites. The majority of the cited references focus on the most notable research, studies of novel applications, and scientific advancements in the field of nanostructures and functional materials employed in oncological therapies over the last six years. Certainly, there are additional stimuli with research potential that can facilitate the drug’s release upon activation, such as reactive oxygen species (ROS), various enzymes, ATP level, or hypoxia; however, our review exclusively addresses the aforementioned stimuli presented in a comprehensive manner.